Variation of Neonatal Outcomes and Care Practices for Preterm Infants <34 Weeks' Gestation in Different Regions of China: A Cohort Study - Ruimiao Bai (Frontiers Media S.A., 2021)
Background: To compare outcomes and care practices of preterm infants born at <34 weeks' gestation in the different regions of China from 2015 to 2018.Methods: This cohort study enrolled all infants born at <34 weeks and admitted to 25 tertiary neonatal intensive care units across China from May 1st, 2015, to April 30th, 2018. The participating hospitals were categorized into three groups according to their distinct geographic locations: eastern China, central China, and western China. Multilevel mixed-effects logistic regression models were used to assess the independent association between neonatal outcomes and regions.Results: A total of 27,532 infants at <34 weeks' gestation were enrolled in our study. Overall, 14,178 (51.5%) infants were from 12 hospitals in eastern China, 8,069 (29.3%) from 9 hospitals in central China, and 5,285 (19.2%) from 4 hospitals in western China. Infants in eastern China had the lowest rates of mortality or any morbidity (23.3%), overall mortality (7.6%), in-hospital mortality (3.7%), and discharge against medical advice (DAMA, 6.3%), compared with central (27.8, 11.3, 5.0, and 10.6%, respectively) and western China (37.4, 19.4, 7.7, and 19.4%, respectively). Multilevel mixed-effects logistic regression showed that infants in western China were exposed to the highest risks of mortality or any morbidity, overall mortality, in-hospital mortality, and DAMA. Significant variations of care practices existed in three regions. Infants in central China had the longest duration of the first course of invasive ventilation, the lowest rate of continuous positive airway pressure within 24 h after birth, the lowest rate of breast milk feeding, the latest initiation of feeds, and the longest duration of total parenteral nutrition among the three regions.Conclusions: We identified marked disparities in outcomes and clinical care practices of preterm infants born at <34 weeks' gestation in different regions of China. Targeted quality improvement efforts are needed to improve the outcomes of premature infants in different regions of China.